Mathematical and economic modeling of stages, business processes, and decision-making mechanisms for strategic changes in stakeholder companies of the construction industry - Prykhodko, D.O.; Oksenchuk, R.O.; Ananko, Ye.I.; Bidenko , D.V. (Ways to Improve Construction Efficiency, 2024)
Mathematical and economic modeling is an integral component of the analysis of strategic changes in stakeholder companies within the construction industry, as it enables the formalization of business processes, risk assessment, and forecasting of managerial decision outcomes. Strategic changes require comprehensive justification, which is achievable only through the use of modern modeling methods, including analytical, simulation, and heuristic approaches. The primary objective of mathematical modeling is to formalize decision-making processes, which involve constructing models for resource allocation optimization, evaluating the economic efficiency of strategic decisions, and analyzing interdependencies among key performance indicators. This involves the application of differential equations, stochastic methods, game theory, and other mathematical tools. Economic modeling focuses on assessing macroeconomic and microeconomic factors that influence the strategic decisions of stakeholder companies, incorporating econometric analysis, forecasting, and financial optimization methods. A crucial aspect is the development of models that consider the impact of external factors such as government regulation, market fluctuations, technological innovations, and environmental constraints. One of the key elements in decision-making is the development of algorithms for evaluating the effectiveness of strategic changes, which involves multi-criteria analysis, scenario modeling, and decision-making methods under uncertainty. This is particularly relevant in the construction industry, where long-term investment payback, economic cyclicality, and high capital intensity of projects play a significant role. The use of mathematical and economic models not only enhances the accuracy of forecasting the effectiveness of strategic changes but also ensures their adaptability to dynamic market conditions. Comprehensive modeling contributes to reducing uncertainty in decision-making, optimizing costs, and increasing the competitiveness of stakeholder companies. A synergistic approach to analyzing business processes in the construction industry facilitates the development of effective risk management mechanisms, optimization of supply chains, and improvement of investment program efficiency. The application of digital technologies combined with mathematical and economic modeling creates new opportunities for automating strategic management processes and adapting to changes in the business environment. Thus, the development of modeling methods and their integration into the management activities of construction companies enhances the efficiency of strategic planning and promotes the sustainable development of the industry in response to modern challenges.